Conceptions of literacy : graduate instructors and the teaching of first-year composition - Brewer, Meaghan (Utah State University Press, an imprint of University Press of Colorado, 2019)
""Proposes a theoretical framework for examining new graduate instructors' pre-conceptions about literacy. A qualitative, empirical study in their first year of teaching to describe complex belief systems and how that influences them as teacher-learners. Finding they come with conceptions of literacy that impacts their training"--Provided by publisher"--